Understanding Primary Care Providers' Experience with Lifestyle Behavior Change Recommendations and Programs to Prevent Chronic Disease - Miller, Megan; Locke, Amy; Fuller, Arwen; King Jensen, Jessica (American journal of lifestyle medicine, 2024)
Prescribing lifestyle behavior change is a recommended strategy for both primary and secondary prevention of disease. Programs that support and encourage lifestyle behavior change are available to patients but are underutilized. The purpose of this study was to understand primary care providers (PCPs) experiences and barriers they experience with referring patients to lifestyle behavior change programs at one academic health care system. In-depth semi-structured interviews were conducted with 7 academic PCPs between November 2020 and January 2021. Qualitative analysis identified major themes. Four themes emerged: (1) guideline awareness and adherence, (2) barriers to lifestyle behavior change recommendations, (3) provider role with respect to lifestyle behavior change recommendations, and (4) suggestions to improve utilization of behavior change support. Specific strategies for improvement include revising referral process, educating providers about programs already offered, integrating a team-based approach, and systemizing healthy lifestyle behaviors interventions. The lessons identified through this study highlight the need for systematic prioritization of lifestyle behavior change to decrease certain barriers that providers face when attempting to integrate lifestyle change consistently into their practice.